Fly ash based geopolymer for the adsorption of cationic and nonionic surfactants from aqueous solution â A feasibility study - Siyal, A.A. (Elsevier B.V., 2021)
The discharge of wastewaters containing surfactants and other pollutants from industries is contaminating the world's water resources which needs remediation. This paper describes the adsorption of cationic and nonionic surfactants cetyltrimethylammonium bromide (CTAB) and Triton X-100 (TX-100) using fly ash based geoepolymer adsorbent. pH was varied between 2 and 10. Geopolymer could not adsorb CTAB and TX-100 surfactants. This was due to the low hydrophobicity of the geopolymer and the weak nature of forces involved in the adsorption of cationic and nonionic surfactants. The modification of the geopolymer with suitable metals or compounds could potentially enable it to adsorb CTAB and TX-100 surfactants. Â© 2020 Elsevier B.V.